Management of the Class III malocclusion treated with maxillary expansion, facemask therapy and corrective orthodontic. A 15-year follow-up - Renato Rodrigues de ALMEIDA; Luiz Eduardo ALESSIO JUNIOR; Renata Rodrigues de ALMEIDA-PEDRIN; Marcio Rodrigues de ALMEIDA; Arnaldo PINZAN; Luiz Sérgio VIEIRA (University of São Paulo, 2015)
The facial growth of Class III malocclusion worsens with age, in this case, the early orthopedic treatment, providing facial balance, modifying the maxillofacial growth and development. A 7.6-year old boy presented with Class III malocclusion associated with anterior crossbite; the mandible was shifted to the right and the maxilla had a transversal deficiency. Rapid maxillary expansion followed by facemask therapy was performed, to correct the anteroposterior relationship and improve the facial profile. The patient was followed for a 15-year period, after completion of the treatment, and stability was observed. Growing patients should be monitored following their treatment, so as to prevent malocclusion relapse.